ANALISIS KOMUNIKASI PETANI KARET POLA SWADAYA DI KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Yuliadi Saputra; Roza Yulida; Rosnita Rosnita; Yulia Andriani (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2020)
This research aims to analyze the effectiveness of rubber farmer communications through the identification of internal and external characteristics and the communication process reviewed from elements of communication. This research applied a survey method in two villages in Gunung Toar sub-district through an interview to 83 respondents by using purposive sampling method. The analysis of the scale of Likert used to analyze the level of cosmopolitan and external characteristics. Descriptive analysis used to analyse the communication processes reviewed from communication elements. Characteristics of the internal and external rubber farmers are: 99% of age-productive respondents, 89% male gender, 42% high school educated and undergraduated, 77% have medium land area (0.5 – 2 ha), 71% experienced farming between 11-20 years, 58% have Between 3-4 people, the level of cosmopolitan respondents judged ineffective. The intensity of the respondents’ rubber counseling is quite effective, the accuracy of the counseling channel is quite effective, and information source is quite effective. The communication process consists of extension, farmer group core management, touke, trader and others as source of information. Message in the form of information about farming in the upstream, cultivation, downstream and supporting subsystems. Media is in the form of meetings, WhatsApps, cellphones, brochures, and rubber farmers as communicants. Feedback in the form of agree, ready to try and rejection feedback. The physical environment is in the village office, sub-district office and in the direct field and counseling is held once a week.